The Role of Cultural Content in Teaching Reading Comprehension - Nur Rasmayanti; Abdul Mu'in; Tatu Siti Rohbiah (Journal of English Language Teaching and Cultural Studies, 2022)
This study investigates the role of cultural content in teaching reading comprehension. This research is (1) to analyze the teachers’ way to teach the cultural content in the classroom in teaching reading comprehension; (2) to find out whether teachers have an awareness of the importance of cultural learning in the form of cultural content in learning English; and (3) to find out the teachers’ responses to teach cultural content in reading comprehension. The reseach used qualitative research. The instruments used in this research were documentation, observation, and interviews. This research involves three English teachers as participants of SMKN 02 Rangkasbitung. The research findings show that cultural content on teaching reading comprehension was found to have been applied by the three English teachers. In class X, it was found that the teacher represented international culture in descriptive texts with material on the history of Hagia Sophia. Then, in class XI, it was found that the teacher represented target culture in the procedure text with the material How to Make Sandwich. In class XII, it was found that the teacher represented source culture in descriptive texts with Baduy Culture material. Next, the English teachers have realized the importance of learning cultural content on teaching reading comprehension. The last, the teachers gave a positive response and argued that cultural content can improve student’s learning processes in reading comprehension.